ANALISIS TINGKAT KESEHATAN BANK DENGAN METODE CAMELS DAN RGEC PADA BANK RAKYAT INDONESIA AGRONIAGA PERIODE 2007 - 2016 - RATTIE PRAMESWARI; Henrycus Winarto Santoso; Bambang Budiarto (CALYPTRA, 2018)
Competition of the band world increasingly tight. Every business that is required to have a health level in accordance with the standards set by Bank Indonesia. Assessment of soundness of commercial banks by CAMELS and RGEC method.This study aims to compare the health of PT. BRI Agroniaga Tbk period 2007 - 2016 using this second method. This research is descriptive research with quantitative approach, using the ratio ofCAR, ROA, ROE, NIM, BOPO, and LDR. Testing is done by descriptive statistical test. With ɑ = 5% found no significant difference in Bank Rating.